Facial motion recognition using camera application for movement of mouse (I-sight mouse) - Hasrul Reeza, Mustaffa (2010)
i-Sight Mouse is developed to help detect and track facial movement to able to control mouse application by using machine vision which is webcam. Existing system has been used and still got a lot of work for improvement so that's why i-Sight Mouse is developed. It is used for people with disabilities that are no hands and need to interact with computer just using the movement of head and facial part. Using Extreme Programming for the software development model helped a lot in develops the system. Extreme Programming (XP) is a software engineering methodology, which is intended to improve software quality and responsiveness to changing customer requirements. As a type of agile software development, it advocates frequent "releases" in short development cycles (timeboxing), which is intended to improve productivity and introduce checkpoints where new customer requirements can be adopted. There are 2 modules in this system which is face recognition and face tracking. By implementing image-processing techniques the system is able to do the face recognition process and face tracking process. Face recognition is a module to capture video frame, enhancement the image and do extraction so that it can be verify either it is a face of human or not Face tracking is-based on predicting the place of the feature in the current frame based on its location in previous ones; template matching and some heuristics are applied to locate the feature's new coordinates. By tracking the eyes the system able to operate right clicks and mouse click operation as user blinking their right eye and left eye. The nose tip is tracked to use its movement and coordinates as the movement and coordinates of the mouse pointer.